Navigating Economic Challenges: Strengthening Organizational Capabilities in the Logistics Sector through Competency Development and Remuneration Systems to Enhance Employee Job Satisfaction and Performance - Jonneli, Halimah Husna; Rubiyanti, Rd.Nurafni; Widodo, Arry; Silvianita, Anita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the impact of competency development and remuneration systems on employee job satisfaction and their subsequent influence on employee performance within organizational settings. Utilizing a structural equation modeling (SEM) framework with a partial least squares (PLS) approach, data from employees across diverse industries were analyzed. Results reveal significant positive associations between competency development and employee job satisfaction, as well as between remuneration systems and employee job satisfaction. Furthermore, employee job satisfaction positively correlates with employee performance. The findings underscore the importance of investing in competency development and implementing effective remuneration systems to enhance job satisfaction and subsequently improve employee performance. These insights offer valuable implications for organizations striving to optimize their human resource management practices to achieve heightened organizational effectiveness.